Offshore Platform Operational Risk Management in Extreme Weather Conditions (Collaborate Engineering Daily Book Series, 2025)
Offshore platform operations have a high level of risk due to direct exposure to dynamic marine environmental conditions, especially during extreme weather events such as storms, high waves, and strong winds. This research and study aims to explain the importance of the application of operational risk management in maintaining worker safety, equipment reliability, and production sustainability on offshore platforms. The risk management approach is carried out through the identification of potential hazards, risk level analysis, and the implementation of mitigation strategies which include improving structure design, real-time monitoring systems, and emergency response procedures. In addition, the use of weather prediction technology and sensor-based monitoring systems is an important part of supporting operational decision-making. With the implementation of effective risk management, it is hoped that potential losses due to operational failures can be minimized, while increasing the resilience of offshore infrastructure to the impacts of climate change and increasing the intensity of extreme weather. This study confirms that the integration of engineering, occupational safety, and operational management aspects is the main key in risk management in the offshore industry.
Keywords: Risk Management; Offshore Platforms; Extreme Weather; Operational Safety; Offshore Engineering; Risk Mitigation; System Reliability; Marine Environmental Monitoring; Offshore Work Safety; Offshore Oil and Gas Operations